Frequency of nursing diagnoses in a surgical clinic - Andreza Cavalcanti Vasconcelos; Claudia Germania Alencar de Castro; Durcival Francisco da Silva; Vanessa Juvino de Sousa (Universidade Federal do Ceará, 2015)
Objective: to identify the frequency of Nursing Diagnoses of patients in a surgical clinic. Methods: cross-sectional study, performed with 99 patients in the postoperative of general surgery. Data were collected through a questionnaire validated according to domains of NANDA International, including physical and laboratory examination. Results: 17 nursing diagnoses were found; eight had a frequency higher than 50.0% (infection risk, impaired tissue integrity, constipation risk, anxiety, bleeding risk, acute pain, delayed surgical recovery, dysfunctional gastrointestinal motility). It was observed in all patients the Nursing Diagnostics: risk of infection, impaired tissue integrity and risk of constipation. Conclusion: the frequency of the most prevalent diagnosis is inserted in the domains safety/protection and nutrition, which determines the need to redirect nursing care, prioritizing the patient's clinic.